DAMPAK UKURAN PERUSAHAAN, LEVERAGE TERHADAP FINANCIAL DISTRESS DAN MANAJEMEN LABA (STUDI PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2019) - Idohatun Nasiroh; Hidayatul Khusnah (Universitas Nahdlatul Ulama Surabaya, 2020)
This study aims to examine company size, leverage, on financial distress and earnings management in mining companies. The dependent variables in this study are company size and leverage. The independent variables in this study are financial distress and earnings management. This study uses secondary data, where secondary data is data obtained from annual financial reports listed on the IDX during the 2014-2019 period. The sample in this study were 6 companies. In this study using purposive sampling method and in analyzing the data using the application WarpPLS 6.0. The results of the analysis show that company size with the indicator size has a positive and significant effect on financial distress. Meanwhile, leverage does not have a significant relationship to financial distress. In earnings management, the indicator with size has a positive influence on earnings management. Meanwhile, the indicator leverage does not have a significant relationship with financial distress and financial distress has a negative and significant effect on earnings management.